2015
DOI: 10.1186/s12903-015-0090-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the smear layer removal and erosive capacity of EDTA, boric acid, citric acid and desy clean solutions: an in vitro study

Abstract: BackgroundThe purpose of this study was to investigate the smear layer removal and erosive capacity of various irrigation solutions with sequential use of NaOCl on instrumented root canal walls.MethodsThe root canals of single-rooted teeth were instrumented with ProTaper rotary instrument. Then, the teeth were randomly divided into five experimental groups. The root canals were irrigated with one of the following solutions (5 mL/1 min): 5 % EDTA, 5 % boric acid (BA), a mixture of BA and CA, 2.5 % citric acid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 30 publications
5
19
0
4
Order By: Relevance
“…In 2015, Turk, Kaval, & Sen also observed erosion, despite using EDTA and citric acid for 1 minute, at lower concentrations than in this study, 5% and 2.5% respectively (27) .…”
Section: Discussionsupporting
confidence: 41%
“…In 2015, Turk, Kaval, & Sen also observed erosion, despite using EDTA and citric acid for 1 minute, at lower concentrations than in this study, 5% and 2.5% respectively (27) .…”
Section: Discussionsupporting
confidence: 41%
“…Apesar dessa informação, a maioria dos estudos aqui pesquisados 20 Quando as soluções testadas foram analisadas em diferentes segmentos do dente -terço cervical, médio, e apical-os autores verificaram que a eficiência está diretamente relacionada com: a profundidade de penetração da agulha de irrigação no interior do canal, a curvatura apical e o tamanho do diâmetro apical. Portanto, os terços, cervical e mé-dio, apresentaram-se mais limpos, enquanto que o terço apical, demonstrou-se com maior quantidade de smear layer e menor número de túbulos desobstruídos 30,79,80 .…”
Section: Discussionunclassified
“…A concentração de 5% foi utilizada em um único caso 20 , assim como a concentração de 15% 21 e as concentrações 10 e 20% 22,23 . Em todos os artigos, o EDTA foi conduzido por meio de irrigação com seringa, sendo que em um único estudo, o EDTA entrou em contato com a superfície do dente, por meio de imersão.…”
Section: Métodosunclassified
“…A recent study indicated that 2.5% citric acid solution was the most effective solution in removal of smear layer, 5 % boric acid showed the least effective. 44 Turk et al, has recommended that a combination of boric and citric acid solutions can be mixed for clinical use in order to achieve antimicrobial effect and smear layer removal capacity at the same time. 44 When compared to citric acid and EDTA, boric acid might be considered as alternative chelating agent on the other hand previous studies indicated that very high intakes of boron induced reproductive and developmental toxicity in mice and rats.…”
Section: Discussionmentioning
confidence: 99%
“…44 Turk et al, has recommended that a combination of boric and citric acid solutions can be mixed for clinical use in order to achieve antimicrobial effect and smear layer removal capacity at the same time. 44 When compared to citric acid and EDTA, boric acid might be considered as alternative chelating agent on the other hand previous studies indicated that very high intakes of boron induced reproductive and developmental toxicity in mice and rats. 45 Consequently, further experimental and clinical evaluations are needed to use the material safely.…”
Section: Discussionmentioning
confidence: 99%